Analysis of parameters of laser-induced periodic microstructures (LIPSS) on the surface of stainless steel using autocorrelation functions - Saprykina, Emiliia; Dobrotvorskiy, Sergey; Aleksenko, Borys; Trubin, Dmytro; Moskal, Denys; Martan, Jiri (Національний технічний університет "Харківський політехнічний інститут", 2025)
In modern mechanical engineering, the control of surface quality of components, which directly affects their operational characteristics, is becoming increasingly important. One of the key aspects is the analysis of surface microstructure, particularly its periodicity, as it determines properties such as wear resistance and corrosion resistance. Laser processing is one of the promising technologies that allows the formation of regular microstructures, such as LIPSS (Laser-Induced Periodic Surface Structures). Despite extensive research, the mechanism of LIPSS formation remains not fully understood, and the results often show variable periodicity and orientation. To accurately analyze these structures, mathematical and statistical methods, such as two-dimensional autocorrelation analysis (ACF) and fast Fourier transform (FFT), are required. This study proposes a methodology for evaluating the periodicity of microstructures obtained during laser treatment of metallic samples, using digital video microscopy. The application of two-dimensional autocorrelation and spectral analysis within the Gwyddion environment ensures reproducible and objective assessment of microstructures, while demonstrating the effectiveness of ACF for surface topography analysis. The obtained data show the presence of pronounced periodicity in the studied microstructure and confirm the complexity of the LIPSS formation mechanisms, contributing to accurate quantitative analysis and adaptive control of laser modification processes.

У сучасному машинобудуванні дедалі більшого значення набуває контроль якості поверхні компонентів, що безпосередньо впливає на їхні експлуатаційні характеристики. Одним з ключових аспектів контролю якості є аналіз мікроструктури поверхні, зокрема такої її трибологічної характеристики як періодичность, оскільки це визначає такі властивості, як зносостійкість, оптичні властивості та корозійна стійкість. Лазерна обробка є однією з перспективних технологій, що дозволяє формувати регулярні мікроструктури, такі як LIPSS (лазерно-індуковані періодичні поверхневі структури). Незважаючи на чисельні дослідження, механізм утворення LIPSS залишається вивченим не до кінця, і результати часто демонструють змінну періодичність та орієнтацію отриманих в процесі дослідження мікроструктур. Для точного аналізу цих структур необхідні математичні та статистичні методи, такі як двовимірний автокореляційний аналіз (ACF) та швидке перетворення Фур'є (FFT). У представленому дослідженні пропонується методологія оцінки періодичності мікроструктур, які були отримано під час лазерної обробки металевих зразків. Структури було вивчено за допомогою цифрової відеомікроскопії, після чого був проведений аналіз отриманих зображень поверхні з використанням програмного середовища Gwyddion. Застосування двовимірної автокореляції та спектрального аналізу в середовищі Gwyddion забезпечує відтворювану та об'єктивну оцінку мікроструктур, одночасно демонструючи ефективність ACF для аналізу топографії поверхні.
Аналіз параметрів лазерно-індукованих періодичних мікроструктур (LIPSS) на поверхні нержавіючої сталі з використанням автокореляційних функцій
Keywords: laser processing; LIPSS; autocorrelation analysis; microstructure; лазерна обробка; LIPSS; автокореляційний аналіз; мікроструктура